Досвід впровадження STEM-освіти при вивченні природничо-математичних дисциплін студентами педагогічних спеціальностей - Кайдан, Н. В.; Величко, С. В.; Kaidan, N. V.; Velychko, S. V. (Донбаський державний педагогічний університет, 2021)
У статті обґрунтовано необхідність впровадження ідей STEM-освіти в навчальний процес студентів педагогічних спеціальностей в аспекті нагальної потреби формування креативної та творчої особистості. Розглянуто план проєктної діяльності, що може бути використаний під час самостійної роботи з природничо-математичних дисциплін. Показана мотивація студентів до дослідницької діяльності, завдяки накопиченню ретельно опрацьованої теоретичної бази та отриманого власноруч експериментального матеріалу.

This article describes the necessity of introducing STEM-teaching ideas into the educational process of the students of pedagogical specialties in terms of the overall need for forming a creative and imaginative personality. The plan of project activities, which can be used during the self-study of natural and mathematical disciplines is shown. The paper demonstrates the motivation of students to research activities due to the accumulation of a well-tested theoretical basis and experimentally obtained material.
The experience of implementing STEM-education in the study of natural and mathematical disciplines by students of pedagogical specialties
Keywords: STEM; метод проєктів; природничо-математичні дисципліни; самостійна робота; робототехніка; project method; natural and mathematical disciplines; self-study; robotics